The Historical Past as Hyperreality in Modern Mass Culture (Collective monograph review: Cultgoods: Commercialization of History in Mass Culture. Moscow; Ekaterinburg: Kabinetnyy Uchenyy, 2020. 348 p.) (Филологический класс, 2021)
The project “Cult-goods”, focused on the study of the dynamically changing field of mass culture in the light of Russian reality, played a special role in the formation of the national literary tradition of studying mass literature. It is also noteworthy that the project was originally created as an international one. The presence of a different research perspective allows the project to remain a platform for discussion even when using similar methodological approaches. The project has existed for more than ten years, during which seven international conferences have been organized and four collections of scientific articles and three collective monographs have been published. Conferences have been held every two years, each time highlighting the current trends of the modern literary process, fixing systemic shifts that change the structure of the cultural field. This article is devoted to the analysis of the collective monograph “Cult-goods: Commercialization of History in Mass Culture”, published as a result of the conference of the same name, held in June 2019 at the University of Bologna in Italy.